1991
DOI: 10.1016/0035-9203(91)90041-v
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole versus praziquantel in the treatment of cerebral cysticercosis: clinical evaluation

Abstract: One hundred consecutive patients presenting with symptoms and signs of neurocysticercosis, confirmed by neuroimaging techniques, were randomly assigned to treatment with either praziquantel 50 mg/kg/d for 15 d or albendazole 15 mg/kg/d for 30 d. All patients were treated in addition with steroids for 45 d. Follow-up was for 90 d for response to treatment and at least 1 year for recurrence. Although similar numbers of patients showed no improvement in neuroimaging criteria at 3 months, the response to albendazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 14 publications
0
23
0
3
Order By: Relevance
“…Instead, the dose previously used in hydatid disease (15 mg/kg/day) was used for cysticercosis. The initial length of therapy was 1 month, later reduced to 15 days and 1 week (2,3,14,21,29,55,63,89,90,94,95,98,111). There is limited experience with higher doses of both drugs (1,11,58).…”
Section: Vol 15 2002 Guidelines For Treatment Of Neurocysticercosismentioning
confidence: 99%
“…Instead, the dose previously used in hydatid disease (15 mg/kg/day) was used for cysticercosis. The initial length of therapy was 1 month, later reduced to 15 days and 1 week (2,3,14,21,29,55,63,89,90,94,95,98,111). There is limited experience with higher doses of both drugs (1,11,58).…”
Section: Vol 15 2002 Guidelines For Treatment Of Neurocysticercosismentioning
confidence: 99%
“…35,68 Albendazole destroys 75 to 90% of parenchymal brain cysts and has been shown to be superior to praziquantel in several comparative trials. 11,62,64,73 Another advantage of albendazole over praziquantel is that the former also destroys subarachnoid and ventricular cysts because of its better penetration in CSF, as well as the fact that it can be administered jointly with corticosteroid agents for antiinflammatory therapy. 12,23,48 The introduction of praziquantel and albendazole has radically changed the prognosis in most patients with NCC.…”
Section: Cysticidal Drugsmentioning
confidence: 99%
“…This created confusion among some physicians involved in the care of neurocysticercosis patients, who questioned the benefi ts of praziquantel and even considered that this drug may actually be deleterious in this setting (Kramer 1995 ). Meanwhile, albendazole, another cysticidal drug, was fi rst tested in Mexico and then in other disease-endemic countries, and proved effective for destroying parenchymal brain cysticerci, with the advantages of being cheaper and somewhat more effective than praziquantel (Alarcón et al 1989 ;Cruz et al 1991 ;Escobedo et al 1987 ;García et al 1997 ;Sotelo et al 1988Sotelo et al , 1990Takayanagui and Jardim 1992 ). Some early studies also found a clinical effect on seizure control, with 50-80 % of treated patients being free of seizures compared to 25 % of untreated patients (Del Brutto et al 1992a , b ;Vazquez and Sotelo 1992 ).…”
Section: Trials Of Cysticidal Drugsmentioning
confidence: 97%